1998
DOI: 10.2337/diacare.21.6.902
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Coping Skills Training as Adjunct to Intensive Therapy in Adolescents

Abstract: CST is useful in improving not only an adolescent's metabolic control, but also their quality of life. As more pediatric providers aim for improved control, in adolescents with diabetes, the addition of this behavioral intervention may be helpful in achieving metabolic and life goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(159 citation statements)
references
References 29 publications
(18 reference statements)
5
148
0
6
Order By: Relevance
“…The quality of life and self-efficacy scales were disease specific so comparisons with the non-diabetic population are not appropriate, however mean scores for both were above the midpoint for the scale indicating relatively high quality of life and self-efficacy. These scores were similar to recent studies on young people with Type 1 diabetes (Grey et al, 2000;Grey et al, 1998;Howells et al, 2002). There were though large standard deviations around the mean scores, suggesting that some individuals within the sample were having psychological difficulties.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The quality of life and self-efficacy scales were disease specific so comparisons with the non-diabetic population are not appropriate, however mean scores for both were above the midpoint for the scale indicating relatively high quality of life and self-efficacy. These scores were similar to recent studies on young people with Type 1 diabetes (Grey et al, 2000;Grey et al, 1998;Howells et al, 2002). There were though large standard deviations around the mean scores, suggesting that some individuals within the sample were having psychological difficulties.…”
Section: Discussionsupporting
confidence: 74%
“…There is no precedent for their use with physical activity, however, they are sensitive enough to show significant associations with other variables such as depression (Grey et al, 1998) and HbA 1c (Grossman et al,., 1987;Howells et al, 2002). The PSPP-C has been shown to be sensitive enough detect associations with physical activity in the non-diabetic population (Crocker et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In adolescents, coping-skills training and stress management programs can decrease diabetesrelated stress, enhance social interactions and QOL, and improve metabolic control (Boardway, Delamater, Tomakowsky, & Gutai, 1993;Grey, Boland, Davidson, et al, 1998;Mendez & Belendez, 1997). Similarly, coping-skills training in adults decreases diabetes-related anxiety and avoidance behaviors, enhances coping ability and emotional well-being, and improves self-care and glycemic control (Rubin, Peyrot, & Saudek, 1989;Zettler, Duran, Waadt, Herschbach, & Strian, 1995).…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Grey et al 40 reported the results of a prospective randomized clinical trial conducted to determine whether coping skills training would improve glycemic and psychosocial outcomes in adolescents with type 1 diabetes implementing intensive diabetes management. In these studies, subjects were randomly assigned to receive coping skills training or enhanced education in addition to intensive management of diabetes.…”
Section: Evidence For Coping Skills Training With Children and Adolesmentioning
confidence: 99%